Challenge case of ventricular arrhythmia in young women - Kaputrin, Nur; Rizal, Ardian; Karolina, Wella; Widito, Sasmojo (Heart Science Journal, 2025)
Background: Torsade de pointes (TdP) and ventricular fibrillation can cause rapid mortality. The etiological cause the ventricular arrhythmia must be detected and treated early, especially in the ER. Objective: We report a patient with severe hypokalemia and TdP following the administration of Amiodarone in QT-interval prolongation Case Report: A 32-year-old girl with diarrhea and vomiting for two days arrived to the ED with a seizure with her hand flexed and leg straight down. Her family reported she didn't take prescriptions regularly. She was GCS 224, hemodynamically stable, typical ECG showed extended QTc and her head CT was normal. During observation at the ED, she had seizure and the monitor revealed a Torsade de Pointes (TdP) ) with a pulse rate of 160-180 bpm. She was given Amiodarone and peroral Bisoprolol 5 mg. She returned to sinus rhythm with PVC bigeminy and was admitted to the ICU Laboratory data showed hypokalemia (1.9) improved (2.9) after treatment. Eight hours later, she experienced a TdP without pulse palpability for less than 1 minute, then Ventricular Fibrillation, began CPR, and the doctor in charge gave her a defibrillation operation once. She returned with sinus tachycardia 110-130 bpm. The next day, she was having recurring TdP episodes without a pulse. The doctor conducted CPR and defibrillation and returned with 120-130 bpm sinus tachycardia. The patient consulted a cardiologist and was prescribed lidocaine 1 mg/hour and continued Bisoprolol 5 mg for long QT problem. Observation The seizure ended 12 hours later, the patient was alert, GCS 456, and the ECG showed sinus rhythm with extended QTc. Over the days before discharge, electrocardiography demonstrated reduced QT-interval prolongation. Conclusion: Life-threatening ventricular arrhythmia in a young female can be caused by QT-interval prolongation. It must be diagnosed and treated immediately to avoid mortality.